2016
DOI: 10.1371/journal.pone.0168076
|View full text |Cite
|
Sign up to set email alerts
|

The TRIAGE-ProADM Score for an Early Risk Stratification of Medical Patients in the Emergency Department - Development Based on a Multi-National, Prospective, Observational Study

Abstract: IntroductionThe inflammatory biomarker pro-adrenomedullin (ProADM) provides additional prognostic information for the risk stratification of general medical emergency department (ED) patients. The aim of this analysis was to develop a triage algorithm for improved prognostication and later use in an interventional trial.MethodsWe used data from the multi-national, prospective, observational TRIAGE trial including consecutive medical ED patients from Switzerland, France and the United States. We investigated tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 38 publications
1
15
0
1
Order By: Relevance
“…In addition, since prognostic accuracy was retained across broad clinical phenotypes (children and adults, with bacterial and viral sepsis, with community-acquired and HAIs, from multiple institutions around the world) the models appear to have successfully incorporated the broad clinical heterogeneity of sepsis. The derived discriminatory power of the gene models (AUCs near 0.85) is at least similar to the AUC of proadrenomedullin (0.83) in a recent large prospective trial (TRIAGE study) 8 . Furthermore, the impact of the addition of the severity score to clinical practice could be substantial.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In addition, since prognostic accuracy was retained across broad clinical phenotypes (children and adults, with bacterial and viral sepsis, with community-acquired and HAIs, from multiple institutions around the world) the models appear to have successfully incorporated the broad clinical heterogeneity of sepsis. The derived discriminatory power of the gene models (AUCs near 0.85) is at least similar to the AUC of proadrenomedullin (0.83) in a recent large prospective trial (TRIAGE study) 8 . Furthermore, the impact of the addition of the severity score to clinical practice could be substantial.…”
Section: Discussionsupporting
confidence: 60%
“…Some peptide markers of sepsis severity have been validated (e.g. proadrenomedullin 8 among others 9 ), but these are not yet cleared for clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that the prognostic abilities of various biomarkers in acutely admitted patients in improving risk assessment in EDs [ 4 9 ]. These biomarkers include lactate [ 10 ], copeptin [ 8 , 9 ], pro-adrenomedullin [ 5 , 6 , 11 ], albumin [ 12 , 13 ], C-reactive protein (CRP) [ 14 , 15 ], and soluble urokinase plasminogen activator receptor (suPAR) [ 16 20 ]. However, none of these studies have addressed whether risk assessment that is strengthened by prognostic biomarkers improves patient outcome.…”
Section: Introductionmentioning
confidence: 99%
“…28 Proper triage relies on adequate risk stratification and can be improved by incorporation of prognostic markers. 29 A number of previous investigations examined the prognostic value of the QRS-T angle in various populations, including patients with arterial hypertension, diabetes, CKD, myocarditis, implanted cardiac devices, chronic heart failure, and suspected and confirmed myocardial ischaemia, as well as in the general population. [4][5][6][7][8][9][10][11][12][13][14] Across the spectrum, greater QRS-T angles were associated with increased risk of adverse events, rehospitalizations, and mortality.…”
Section: Discussionmentioning
confidence: 99%